ANALISIS PERBANDINGAN KONSEP ASHNAF FII SABILILLAH DALAM ALOKASI DANA ZAKAT - Eka Sakti Habibullah; Ibdalsyah Ibdalsyah; Erwandi Tarmidzi (Kasaba, 2019)
This thesis will try to explore and compare two opinions about fii sabilillah according to the scholars and their arguments to support. The first opinion of those who restrict their meaning and extent of the mujahideen that support things such as salaries, supplies, etc. Second opinion they are expanding the scope of meaning to each activity fii sabilillah kindness, public facilities (schools, Islamic centers, the remedy market dhu'afa, etc.), activities that are intended to elevate kalimatullah as jihad has the same purpose.